Photovoltaic panel’s angle optimization for a better reflected irradiation collection using empiric data and Excel functions approximation - Ivan, Tudorel; Cristea, Ovidiu (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
There are many unused surfaces (places) where is practical to install PV panels and still there is a lack of research in this domain. That is why this article presents research for a single row, from W-E, PV panels module output at different installation angle for a better indirect radiation collection, in special areas, like: roof, water-surface and shore. It contains experimental data correlated with simulation data.